Download presentation

Published byJoy Sandra Doyle Modified over 7 years ago

1
**9.4 – Solving Quadratic Equations By Completing The Square**

2
Ex. 1 a. Solve x2 – 12x + 36 = 0.

3
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0

4
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x )(x ) = 0

5
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0

6
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 (x – 6)2 = 0

7
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 √(x – 6)2 = √0

8
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 √(x – 6)2 = √0 x – 6 = 0

9
Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 √(x – 6)2 = √0 x – 6 = 0 x = 6

10
b. Solve x2 + 8x + 16 = 0.

11
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 √(x + 4)2 = √ 0 x + 4 = 0 x = -4

12
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square.

13
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0

14
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 Want x2 + 10x + 25

15
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4

16
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4 (x + 5)2 = 4

17
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2

18
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x + 5 = 2

19
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x + 5 = 2 x + 5 = -2

20
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x + 5 = 2 x + 5 = -2 x = -3

21
b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x + 4 = 0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x + 5 = 2 x + 5 = -2 x = x = -7

22
**b. Solve x2 + 14x = 12 by completing the square.**

23
**b. Solve x2 + 14x = 12 by completing the square.**

Want x2 + 14x + 49 x2 + 14x + 49 = 61 (x + 7)2 = 61 x + 7 = ±√61 x = -7 ± √61 x ≈ 0.8 or x ≈ -14.8

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google